Adoption of weather index insurance: Learning from willingness to pay among a panel of households in rural Ethiopia - Hill, Ruth Vargas; Hoddinott, John F.; Kumar, Neha (International Food Policy Research Institute, 2011)
In this paper we examine which farmers would be early entrants into weather indexinsurance markets in Ethiopia, were such markets to develop on a large scale. We do this by examining the determinants of willingness to pay for weather insurance among 1,400 Ethiopian households that have been tracked for 15 years as part of the Ethiopia Rural Household Survey. This provides both historical and current information with which to assess the determinants of demand. We find that educated, rich, and proactive individuals were more likely to purchase insurance. Risk aversion was associated with low insurance take-up, suggesting that models of technology adoption can inform the purchase and spread of weather index insurance. We also assess how willingness to pay varied as two key characteristics of the contract were varied and find that basis risk reduced demand for insurance, particularly when the price of the contract was high, and that provision of insurance through groups was preferred by women and individuals with lower levels of education.